Penyaluran Kredit dan Tingkat Likuiditas: Bukti Empiris pada Bank Umum di Indonesia - Arnoldus Hesron Bhoka; Sari Yuniarti; Mohammad Burhan (University of Merdeka Malang, 2021)
This paper examines the effect of bank lending on liquidity. We use the loan-to-deposit ratio as a proxy for liquidity and total loan as a proxy for bank lending. We also consider the measurement of liquidity with non-performing loans (NPL) and return on assets (ROA) as control variables. The sample used is the banks listed on the Indonesia Stock Exchange as many as 42 banks with a total of 184 observations from unbalanced panel data. The analysis used is panel data regression (generalized least squares) with random effects as the best estimation model. We find bank lending to have a positive effect on liquidity, especially for banks that go public. We argue that banks avoid bankruptcy by increasing the proportion of reserves to absorb risk. The results support the “risk absorption” hypothesis (Berger Bouwman, 2009). We also find that return on assets (ROA) has a significant effect on liquidity, but non-performing loans (NPL) have no significant effect on liquidity, proving that banks has managed their reserves by absorbing risk properly.